Про походження амфор типу «Солоха» - Гарлан, І. (Археологія, 1992)
У статті пропонується нова гіпотеза походження амфор типу «Солоха». На основании новых данных археологических раскопок и известных литературных памятников автор выдвигает свою гипотезу о происхождении амфор «Солоха». Проанализировав пепаретские амфоры, исследователь приходит к выводу, что амфоры из кургана «Солоха» на побережье Черного моря (ранее считавшиеся неизвестными по происхождению) также походят из Пепаретоса. Для обоснования своей точки зрения автор рассматривает: типологию, размеры, тесто, энглифичные круги, клеймение, датировку и распространение амфор. Proceeding from the data of archaeological excavations as well as from the well-knom literature materials the author puts forward his own hypothesis on the origin of the «Solokha» amphoras. Having analyzed the Peparethian amphoras he comes to the conclusion that amphoras from burial mound «Solokha» on the coast of the Black Sea which were previously considered to be of unknown origin are also stemmed from Peparethos. To confirm this standpoint the author analyzes typology, dimensions, paste, englyphic circlec, marking, dating and spreading of the amphoras in question.